Building the adaptive capacity of institutions towards managing climate security: a social learning approach - Medina, Leonardo; Schapendonk, Frans; Caroli, Giulia; Pacillo, Grazia; Hellin, Jonathan; Läderach, Peter R.D.; Bonatti, Michelle (Bioversity International and the International Center for Tropical Agriculture, 2022)
The complex nature of climate-related security risks is widely recognized as embodying a collective action problem, thereby requiring a diverse set of actors to mitigate such risks. However, the exact makeup of actor coalitions and the mechanisms to integrate multi-sectoral approaches in programming solutions remain something to be explored under distinct governance systems. This article presents a practical methodological approach to overcome these challenges building upon social learning theory, to foster institutional innovation towards governance systems that are more responsive to climate-related security risks. Social learning is proposed as a governance mechanism to develop multi-stakeholder communities of practice that facilitate climate security-sensitive policies, strategies, and programmes. Outputs from an applied reflexive dialogue evidenced how such a coalition of actors can strengthen capacities to develop locally-owned and adaptive climate action interventions that consciously work to mitigate climate-related security risks.